CLONAL FIDELITY STUDIES ON REGENERANTS OF PSOPHOCARPUS TETRAGONOLOBUS (L.) DC. USING RAPD MARKERS - E. P. KOSHY,; B. K. ALEX,; P. JOHN, (The Bioscan, 2013)
The molecular marker based methods are highly preferred over other methods to assess the clonal fidelity and genetic polymorphism. In this study, Random amplified polymorphic DNA (RAPD) markers were used to amplify DNA from invitro propagated plantlets ofPsophocarpus tetragonolobus (L.) DC (Winged Bean) for evaluating the genetic stability. Seventeen arbitrary decamer primerswere used to find out the RAPD patterns existing in parent plant and in vitroregenerated plantlets. These 17 primers (C61-C77) yielded 170 products of which 44 were polymorphic (that is, 25.88% polymorphism).The dendrogram based on the Unweighted Pair Group Methodwith Arithmetic average (UPGMA) cluster analysis and Nei’s similarity index depicted that the parent plant and the in vitro cultured plants have high degree of similarity.